An extraordinary survival at the age of 67 years in an unoperated case tetralogy of Fallot presenting as systemic hypertension despite RV dysfunction. (28th January 2014) - Prakash, Sadashivappa Surhonne; Sharma, Rajni; Agrawal, Navin; Shankar, Somanna
Abstract : Tetralogy of Fallot is a cyanotic congenital heart disease characterised by a tetrad of four anomalies including ventricular septal defect, pulmonary stenosis, over-riding of aorta and right ventricular hypertrophy with high incidence of infant and early childhood mortality with middle age survival less than 5%. Most cases require treatment in infancy and are symptomatic early on. Rare cases of survival to middle age have been reported especially after the fourth decade. We report an unoperated case of tetralogy of Fallot diagnosed at the age of 67 which is one of the longest time periods of diagnosis of a life-threatening congenital heart disease. Despite tetralogy and having right ventricular dysfunction manifested in the form of congestive symptoms, this patient presented with systemic hypertension along with cyanosis and clubbing which is considered to be a relatively rare presentation in this syndrome. The patient wished to be managed conservatively.